Digital supportive supervision (DiSS) of maternal health, child health and nutrition (MCHN) service delivery in Rajasthan, India: study protocol for impact evaluation and cost-effectiveness analysis - Anurag Joshi; Anil Agarwal; Shankar Prinja; Shweta Sharda; Aarti Goyal; Pranav Kshtriya; Praween Kumar Agrawal; Prakash Singh; Ajay Trakroo; Luigi D'Aquino; Shubhra Singh; Raghuraj Singh (BMJ Open)
Background A digital supportive supervision (DiSS) tool was developed and implemented in Rajasthan, India, to enhance the coverage and quality of maternal health, child health and nutrition (MCHN) services. This study aims to assess the impact and cost-effectiveness of DiSS compared to traditional paper-based supportive supervision.Methods and analysis A quasi-experimental research design incorporating interrupted time series regression analysis will be employed to evaluate the impact of DiSS. Two districts from the high DiSS intensity group, defined as having at least 25% of the MCHN sessions supervised digitally, will be randomly selected as intervention districts. Two comparator districts will be selected from the low DiSS intensity group (less than 25% of MCHN sessions supervised digitally) after matching with intervention districts based on three indicators—female literacy, proportion of population belonging to scheduled caste or tribe and coverage of four antenatal care visits. District-level monthly data on the number of beneficiaries using MCHN services will be obtained from the state’s routine health management information system. Key informants involved in supervising MCHN sessions will also be interviewed to complement the quantitative findings. A mixed micro-costing methodology, incorporating top-down and bottom-up approaches, for assessing the cost of implementing supervision in either scenario. A decision model will estimate long-term health outcomes, in the form of quality-adjusted life years (QALY), in both the intervention and comparator groups. Cost-effectiveness of DiSS will be assessed by computing the incremental cost per QALY gained in the intervention versus comparator group.Ethics and dissemination The study has been approved by the Institute Ethics Committee of the PGIMER, Chandigarh, India (IEC No. IEC-03/2023–2671). The study results will be disseminated at research conferences and published in peer-reviewed journals.